Teaching work, gender and neoliberal and neoconservative policies: a critical reading of the Common National Base for teacher training of Basic Education (Práxis Educativa, 2020)
This paper identifies, describes and analyzes changes in teaching work in the current Brazilian context in the face of the advancement of neoliberal and neoconservative policies. For that, the proposal for a Common National Base for Teachers Training of Basic Education (CNBTT – CNB Training – CNB Teachers) is assumed as a privileged object of analysis. Critical reading is based on teaching studies, gender studies and contemporary social theory, especially in those approaches related to cognitive capitalism and neoliberalism as organizing rationalities of ways of life and work relationships. The analyzes point to the intensification of an educational agenda directed in an increasingly expressive way towards the constitution of a standardized, generalist and multipurpose teaching. At the same time, it becomes possible to multiply the meanings produced by the CNBTT to create pedagogical alternatives based on new ways of interpreting teaching in the 21st century, defining it as an exercise of pedagogical love.Keywords: Teaching work. Gender. Common National Base.